PERANCANGAN CORPORATE IDENTITY “DAILYUSE” PADA CV ADHI BUMI LESTARI - Iman Saufik Suasana; Zumroasih Zumroasih (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2021)
Corporate Identity is the identity of a company which consists of visual identity (name, logo, trademark, typography, color, etc.) and verbal identity (slogan, tagline, etc.). Corporate identity is an active effort to build an image within the company. One example of a company that requires a corporate identity as a new image builder and to introduce it to the public is the clothing company CV ADHI BUMI LESTARI. Where this company is a new company engaged in the clothing vendor (sewing, screen printing and computer embroidery). In an effort to increase sales, the company makes advertisements and promotions through various media such as visual and print media. New companies will compete to get attention from customers or target markets, so companies need to make their company different from other companies by creating an image so that the company is easily recognized and remembered by the public. The existence of the corporate identity of the company is considered unable to present the company's vision and mission. The visual form of the company's identity does not reflect the image to be conveyed. Therefore, to deal with these problems and shape the public's visual of the daily use brand, a graphic system that describes the corporate identity is needed through the formation of a new corporate identity. Through research methods and data obtained through observations, interviews and literature.